(untitled) (The International Journal of Educational Sciences and Arts, 2024)
Bread is the basic food for the peoples of the world, and it is a basic pillar of food security and it cannot be dispensed with or considered complete food security without securing the source of bread (tahini), which is usually made from wheat flour, but alarm bells are starting to sound regarding the adequacy of this product, as the population increase continues It increased demand, and other signs of danger appeared on the horizon, such as climate changes and the efforts of producing countries to adopt special methods in marketing and prices, as well as health warnings issued by doctors and nutrition experts from time to time. Economical and safer in terms of health. These alternatives exist and are used effectively in the world, but they are still on a small scale, including Shear bread, corn bread, oat bread, buckwheat bread, potato bread and sweet potatoes. In terms of relieving pressure on wheat as the only source for the bread industry, the problem of the study is summarized in the following question (Is relying on other sources of grains and vegetables effective? Barley, corn, oats, buckwheat, potatoes, and sweet potatoes in the bread industry will contribute to adding new types of bread to the consumer, thus relieving pressure on wheat as the only source for the bread industry? Certainly, and therefore, it will contribute to strengthening Saudi food security and expanding the options of the political decision-maker. In her study, the researcher relied on the analytical research method, which is an approach based on the analysis of the special forces of the state, including raw materials, manufactured, and semi-manufactured goods, and is concerned with the economic aspect in the agricultural, industrial and health fields. The structure of the study has three sources, namely: the first/ the role of bread in food security, the second/ sources of bread and new mixtures and their nutritional value, third/ the possibility of diversifying the sources of bread in the Kingdom of Saudi Arabia.